The influence on vendor evaluation criteria by the characteristics of officer in ICT projects procurement at Ministry of Education Malaysia / Azran Ahmad - Ahmad, Azran (2014)
This study was conducted to analyse the identified factors that influence vendor evaluating criteria for Information Communications Technology (ICT) projects in the Ministry of Education (MOE). The factors are based on the MOE initiatives to strengthen ICT procurement procedures and the vendor evaluating criteria determined by a literature review. A sample of 240 people who represented the target population involved in this research which covered the MOE officer at various groups of officer's designation, officer's level of offices, gender, type of procurement committee and the frequency of officer's involvement in procurement committee. That officer's character was conceived as the identified factors in this study. Prime data were gathered through online questionnaires and analysed by computer using software of SPSS version 21. The analysis that was done - Descriptive Statistics presented in frequencies for the analysis of One-Way ANOVA and Independent ʈ-Test. The outcome of the research was presented as the average scores of vendor evaluating criteria are not statistically different by the influence of groups of officer's designation factor and the type of procurement committee factor, but significant difference in factor of officer's gender, the factor of office's level and factor of frequency of officer's involvement in procurement committee. Meanwhile, vendor evaluation scores given by officers of all groups were breached and independent of the priority items that were specified among the items of the group. The finding was crucial for MOE, in particular to the Procurement Committee to obtain a fuller understanding of indirect factors that determine the choice of ICT vendors in MOE, so that the assignment of vendor to pack out the ICT projects in MOE will be safer, thus contribute towards the output of quality ICT products in fulfilling the needs of the present users.